A Critical Discussion of the Consequences of Using Blackboard in Second/Foreign Language Education at Tertiary Level - Hasegawa, Hiroshi (Common Ground Publishing LLC, 2010)
In order to utilise technological developments and handle increasing demands for flexible learning, it is common nowadays in tertiary education for the use of e-learning to be advocated to support teaching and learning activities. Blackboard is one aspect of e-learning which has been introduced widely. While there are many advantages in its use, the practice has also given rise to various obstacles and created some dilemmas for educators in second/foreign language education. This paper will describe these dilemmas. The first part discusses the current situation in the tertiary second/foreign language educational environment, where the use of Blackboard is reducing opportunities for the interpersonal interaction which is essential to effective learning, and the consequences of this. The second part presents some statistical evidence about language students’ access to Blackboard. The third part of the paper suggests some strategies for tackling the obstacles that have been identified. What sets this paper apart from others which describe the merits and insufficiencies of technological developments in Blackboard is its focus on obstacles experienced directly by the author over the delivery of a second/foreign language unit in 2009, when the Blackboard teaching/learning support system was officially standardised at the author’s institution, and the discussion of these obstacles from both theoretical and pragmatic perspectives.